Transforming Communication Patterns in Digital Society through Social Media - Mutiarin, Dyah; Sabarofek, Luis Armando (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines how social media transforms communication patterns in digital society, shifting from traditional interaction to networked, participatory communication. Using a descriptive qualitative approach, this research conducts a systematic literature review guided by the PRISMA framework and draws on data from Scopus-indexed publications. NVivo 12 Plus was employed to identify key themes and relationships across the literature. The findings reveal that social media functions not only as a communication tool but as a dynamic communication ecosystem that fosters participation, strengthens social connectivity, and reshapes digital culture. Dominant themes include communication, media, civic engagement, and digital literacy, indicating the growing influence of social media in structuring human interaction. The study also highlights critical challenges, including issues of privacy, ethics, and unequal digital literacy. Overall, this research contributes to the development of digital communication studies by providing a contextual understanding of social media’s role in Indonesia and offering insights for future policy and research on sustainable digital communication ecosystems.